Analysis of an i-Pad initiative: Are students using the technology? - DuBose, Cheryl O.; Amienyi, Sanoya; DuBose, Brittany (Journal of Interdisciplinary Studies in Education, 2017)
This study follows the implementation of an iPad Initiative program at a university in the mid- south region of the United States. Freshmen students enrolled in a First Year Experience (FYE) course within the College of Nursing and Health Professions (CNHP) were surveyed regarding iPad use and curriculum implementation. Research questions included which apps are most popular for personal and school related use, which courses most commonly use the iPad, and whether students are satisfied with the current level of iPad integration within the curriculum.